Mario Sironi and Italian modernism : art and politics under fascism - Braun, Emily, 1957-; Sironi, Mario, 1885-1961. (New York, N.Y. : Cambridge University Press, 2000)
This book examines the work of Mario Sironi, painter, caricaturist, designer, and muralist, whose images shaped the political myths of Italian Fascism. Providing a case study of the relationship between artistic freedom and political authoritarianism during and between the world wars in Italy, Emily Braun's study challenges traditional interpretations of this period as a 'return to order'. Recounting how Sironi fashioned the Fascist regime's image in both high and low-art forms, from propaganda in the press to monumental mural projects, Braun shows why Sironi was defended by progressive critics, and even Mussolini himself, as the consummate artist of the 'Fascist Revolution'. Both a monograph and cultural history, Mario Sironi and Italian Modernism charts the fate of modern art and the avant-garde project of cultural renewal under Fascism. It reveals the relationship between Fascism, myth and modernism, as well as the link between Sironi's art and post-war abstraction in Europe and America.
1. Sironi in context -- 2. Sironi futurista -- 3. The urban landscapes -- 4. Melancholy and the modern allegory -- 5. Sironi and the Novecento -- 6. Bodies mythic and politic -- 7. Artist of the Fascist revolution -- 8. The politicization of aesthetics -- 9. Fascism, myth, and modernism.
Includes bibliographical references (p. 289-303) and index.
The Roger Griffin ComFas Collection
Keywords: Sironi, Mario, -- 1885-1961 -- Criticism and interpretation; Fascism and art -- Italy